2021
DOI: 10.3390/su13041904
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Recent Developments of Green Banking in Bangladesh

Abstract: This paper aims to explore the emergence of ‘Green Banking’ in Bangladesh, with a focus on the role of financial regulation and regulators in greening the financial sector. It also examines the contribution and involvement of banks and non-bank financial institutions in promoting green economic transition. The study is based on the review of secondary data collected from various sources, such as quarterly reports, annual reports, websites of the central bank of Bangladesh, and other commercial banks and non-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 57 publications
7
74
0
Order By: Relevance
“…Consequently, the empirical findings revealed that the banks' total green financing rose by 7.26% during the pandemic compared to the previous year, contrasting the 18.53% decrease experienced by NBFIs during the same period. This result is consistent with the recent study of Khairunnessa et al, (2021) that, contrary to the NBFIs, banking institutions in Bangladesh had improved during the past year in terms of green financing. Moreover, the overall banks' green financing of various projects such as green establishment, green brick manufacturing, renewable energy, energy efficiency, recycling & recyclable product and others were estimated to be BDT 105920.18 Million in 2020, which exceeded the amount (BDT 98753.04 million) invested in 2019.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consequently, the empirical findings revealed that the banks' total green financing rose by 7.26% during the pandemic compared to the previous year, contrasting the 18.53% decrease experienced by NBFIs during the same period. This result is consistent with the recent study of Khairunnessa et al, (2021) that, contrary to the NBFIs, banking institutions in Bangladesh had improved during the past year in terms of green financing. Moreover, the overall banks' green financing of various projects such as green establishment, green brick manufacturing, renewable energy, energy efficiency, recycling & recyclable product and others were estimated to be BDT 105920.18 Million in 2020, which exceeded the amount (BDT 98753.04 million) invested in 2019.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the empirical findings revealed that the total number of branches with an online coverage increased by 4.55%, 0.6% and 1.54% for PCBs, SOCBs and FCBs respectively during the pandemic. On the other hand, the number (percentage) of online branches slightly decreased for the PCBs and SOCBs during this pandemic, while that of FCBs remained unchanged, which is consistent with the past studies (Akter et al, 2018;Hoque et al, 2019;Khairunnessa et al, 2021;Zheng et al, 2021). These studies highlighted that the green banking in Bangladesh had improved in recent years, especially in terms of green funding and in-house risk management, which is largely promoted by the BB in a bid to green the Bangladeshi banking system.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations